Pintu Pintar Menggunakan RFID 522 Berbasis Arduino Uno - Handika Sanjaya; Juni Triyanto; Refdi Andri; Phito Prima Sanjaya; Teguh Pratama Vinta Viano; Fitri Yani (Universitas Harapan Medan, 2021)
In the current pandemic period of crime is increasing. There are many crimes such as theft, home burglary and so on. Therefore the function of a door plays a very important role as one of the protectors at home. Currently the door generally still uses a manual key, although there are some who have used the door with a layered level of security but not evenly distributed. Even in big cities not all people have doors with double safety. The increasing development of technology also affects the development of a door. Many technologies are created with the aim of protecting residences from crime actions where one of them is to make sophisticated security on the door. In this study a more practical door safety was made for users by utilizing RFID 522 and Arduino Uno. The research method used is research and development. This method applies research procedures that are divided into 9 stages. The purpose of this tool is made to increase security on the door so it is not easy to break by people who want to commit crimes. The results of this study are using the ID Card Card Code, where if the card code reads 131.41.129.2 then the door will open but if the card code reads 249.128.96,211, the key is not open